2019
DOI: 10.1111/cobi.13232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of law enforcement and community outreach on mammal diversity in a biodiversity hotspot

Abstract: Management activities such as law enforcement and community outreach are thought to affect conservation outcomes in protected areas, but their importance relative to intrinsic environmental characteristics of the parks and extrinsic human pressures surrounding the parks have not been explored. Furthermore, it is not clear which is more related to conservation outcomes—the management itself or local people's perceptions of the management. We measured objective (reports by park staff) and subjective (reports by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…We obtained a high number of independent records of muntjac ( n = 358) with a mean probability of occurrence of 0.46 (Table ), indicating prey for medium‐ to large‐sized carnivores was abundant. However, muntjac is a primary target for human hunting throughout Southeast Asia (Damania et al , 2008; Harrison et al , 2016; Chen et al , 2019). According to our local guides, muntjac hunting (mainly with snares) is already prevalent in our study area, and this may quickly lead to prey depletion for many carnivores, especially for endangered Bengal tiger.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained a high number of independent records of muntjac ( n = 358) with a mean probability of occurrence of 0.46 (Table ), indicating prey for medium‐ to large‐sized carnivores was abundant. However, muntjac is a primary target for human hunting throughout Southeast Asia (Damania et al , 2008; Harrison et al , 2016; Chen et al , 2019). According to our local guides, muntjac hunting (mainly with snares) is already prevalent in our study area, and this may quickly lead to prey depletion for many carnivores, especially for endangered Bengal tiger.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown PAs to be disproportionately placed in economically marginal lands to reduce opportunity costs, rather than in the most biodiverse areas (Venter et al, 2018). A positive association between mammal diversity and PA coverage could be observed even if diversity is declining in PAs (Chen et al, 2019), necessitating an assessment of trends in diversity inside and outside of PAs, and ideally before and after their establishment, to more rigorously evaluate effectiveness. While previous work has demonstrated effective protection by PAs of forest cover (Naughton-Treves et al, 2005) and habitat structure (Geldmann et al, 2013;Joppa et al, 2008), our study indicates that those benefits extend to mammal communities.…”
Section: Discussionmentioning
confidence: 99%
“…The Indochinese tiger Panthera tigris corbetti (Linnaeus, 1758), the Indochinese leopard Panthera pardus delacouri (Pocock, 1930) and the dhole Cuon alpinus are of great conservation importance in China and globally. To our knowledge, camera-trapping efforts in Xishuangbanna have not recorded any tigers since c. 2010 (Feng et al, 2008), and leopards and dhole are currently rare (Laguardia et al, 2017;Chen et al, 2019). The interviewees stated that 'tigers and leopards were considered as pests in the past because they used to attack and steal the local cattle, pigs and poultry'.…”
Section: Tales From the Past And The Presentmentioning
confidence: 99%
“…Historically, the major local ethnic groups, the Dai, Hani and Akha, hunted in the forest to supplement their rice-based agricultural production (Hu et al, 2008). The current local economy is well developed due to the production of rubber and domestic protein sources are affordable and widely available, but hunting continues (Fan, Fei & Luo, 2014;Sreekar et al, 2015aSreekar et al, , 2015bChang et al, 2017Chang et al, , 2019Chen et al, 2019). Despite the fact that gun ownership has been illegal in China since 1996, local villagers still hunt with guns for sport and because they prefer to consume wild meat ( Fig.…”
Section: Study Areamentioning
confidence: 99%